A Simple Wide Range Approximation of Symmetric Binomial Distribution - Tamás Szabados (Entropy)
The paper gives a wide range, uniform, local approximation of symmetric binomial distribution. The result clearly shows how one has to modify the classical de Moivre–Laplace normal approximation in order to give an estimate at the tail as well as to minimize the relative error.